Labor field and educational services: interaction of two markets within professional education - Ilyina, I.V.; Tsakhaeva, A.A; Smelov, P.A.; Zaytseva, O.Yu.; Panfilova, V.M.; Eshinimaeva-Shagdarova, E.T. (Opción, 2019)
The aim of the study is to investigate serious marketing research of educational services market from professional educational institutions that should lead to perfection of managing educational services via qualitative comparative analysis as a method. In result, the system of professional education is a non-linear open system having a dynamic interaction with the surrounding world being able to conduct self-analysis, quantitative and qualitative enrichment and permanent transformation which continuously take place in outer and inner environment. In conclusion, modern education is characterized by a wide choice and high competitiveness of educational services being rendered by state and non-state educational institutions.